2019
DOI: 10.1109/access.2019.2910592
|View full text |Cite
|
Sign up to set email alerts
|

Interference Analysis and Filter Parameters Optimization for Uplink Asynchronous F-OFDM Systems

Abstract: Filtered-orthogonal frequency division multiplexing (F-OFDM) is a candidate for 5G new waveform, which has flexible numerologies to support various scenarios and can combat interference of multi-users effectively with filters. However, although longer filter length and higher roll-off factor can suppress out of band radiation, inter-symbol interference (ISI) and inter-carrier interference (ICI) will increase at the same time. Meanwhile, the wider guard band reduce inter-user interference (IUI) at the cost of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Last but not least, the proposed INI management technique with a cross-layer approach can be applied to other spectrally enhanced OFDM systems [40]- [43] as well by optimizing the waveform parameters and guards along with a proper scheduling mechanism. For example, a recent publication [18] demonstrated the joint optimization of the filter parameters and guard band for filtered-OFDM (f-OFDM) only in the PHY layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, the proposed INI management technique with a cross-layer approach can be applied to other spectrally enhanced OFDM systems [40]- [43] as well by optimizing the waveform parameters and guards along with a proper scheduling mechanism. For example, a recent publication [18] demonstrated the joint optimization of the filter parameters and guard band for filtered-OFDM (f-OFDM) only in the PHY layer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that it is a new interference type, which will be an issue for 5G, extensive research led to in-depth INI analyses and various INI management techniques [12], [15]- [22]. For instance, windowing [16], [17] and filtering [18], [20] operations are performed at both transmitter and receiver side along with the guard band allocation to mitigate the unwanted emissions from nonorthogonal numerologies. In addition, it is demonstrated that mixed transparent waveform processing can be applied to optimize the complexity-performance trade-off at transmitter and receiver separately [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ao ajustar seus dois parâmetros independentes, pode-se controlar alguns parâmetros espectrais, como a HMLW e MSLL para várias aplicações. Recentemente, a janela Kaiser foi utilizada em um modelo de otimização de parâmetros do filtro sinc-janelado em um sistema uplink f-OFDM multiusuário, com o objetivo de aumentar a eficiência espectral desta tecnologia [7].…”
Section: Funções De Janela E Aplicações Em Esquemas De Modulação Ortogonalunclassified
“…Yang et al [15] proposed an F-OFDM waveform with two sub-bands (users) in uplink asynchronous transmission to achieve the BER objective and SE enhancement using a window-sinc filter. For various numerologies between the users, the authors derived the theoretical computation of BER on ISI, ICI, and IUI.…”
Section: Literature Reviewmentioning
confidence: 99%